2022
DOI: 10.3947/ic.2021.0132
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization andin vitroEvaluation of Specific Bacteriophages Targeting Extensive Drug Resistance Strains ofPseudomonas aeruginosaIsolated from Septic Burn Wounds

Abstract: Background Antibiotic resistant bacteria and various infections caused by them especially extensive drug resistance (XDR) strains and worrying statistics of mortality due to these strains and also the lack of a clear vision for development and production of new effective antibiotics have made the necessity of using alternative therapies more apparent. Materials and Methods In this study, specific phages affecting the Pseudomonas aeruginosa XDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, the phage cocktails were more effective at reducing all S. Choleraesuis strains than individual phages. Several studies have shown consistent findings [68][69][70][71]. Phage cocktails may remedy the problem of a narrow host range.…”
Section: Discussionmentioning
confidence: 76%
“…However, the phage cocktails were more effective at reducing all S. Choleraesuis strains than individual phages. Several studies have shown consistent findings [68][69][70][71]. Phage cocktails may remedy the problem of a narrow host range.…”
Section: Discussionmentioning
confidence: 76%
“…Compare to the standard of care, the bacterial count was decreased and less serious adverse effects were observed in phage cocktail-treated individuals. Marashi et al 15 isolated PaBa1, PaBa2, and PaBa3 phages from the Myoviridae and Podoviridae families against XDR strains of P. aeruginosa , causing burn infections. Phage PaBa1 and the phage cocktail prepared from the three mentioned phages were able to lyse 62.5% and 67.5% of P. aeruginosa strains, respectively.…”
Section: Introductionmentioning
confidence: 99%